Strategi Manajemen Agribisnis: Pemanfaatan Limbah Pertanian untuk Produksi Pupuk Organik Tanaman Hortikultura - Tesya Lola Otovia; Lokot Muda Harahap; Chelsy Nainggolan; Dian Putri Islami Br Sebayang; Jhonatan Fidei Lafau; Nabila Al Zahra Ginting (CV. ITTC INDONESIA, 2026)
This study aims to analyze agribusiness management strategies for utilizing agricultural waste to produce organic fertilizer for horticultural crops. This research used a qualitative approach with a literature review method. Data were obtained from various sources, such as books, scientific journals, and research articles related to agribusiness, agricultural waste management, organic fertilizer, and horticultural crop cultivation. The results indicate that agricultural waste, such as rice straw, plant stems, dried leaves, and harvest residues, has significant potential for use as raw materials for organic fertilizer because it contains essential plant nutrients. Utilizing organic fertilizer from agricultural waste can improve soil fertility, increase the growth and productivity of horticultural crops, and reduce dependence on chemical fertilizers. Furthermore, processing agricultural waste into organic fertilizer also provides economic benefits for farmers by reducing production costs and opening up new business opportunities. Therefore, implementing appropriate agribusiness management strategies for agricultural waste management is crucial to support a more efficient and sustainable agricultural system.